Answer:
The required equation models the total profit, y, based on the number of hot dogs sold, x is y = 3 x - 30.
Explanation:
Let x = total number of hot dogs sold
y = total profit from total sales of hot dogs
The given situation can be written as: y = m x + C ......[A]
Now, Profit for 40 hot dogs = $90 profit
So, here this can be written as:
90 = 40 m + C ......[1]
Profit for 80 hot dogs = $210 profit
So, here this can be written as:
210 = 80 m + C ......[2]
Now, solving both the equations, we get:
Subtracting [1] and [2], we get
210 - 90 = 80 m + C - (40 m + C)
or, 120 = 40 m
or, m = 120/40 = 3
or, m = 3
Solving for the value of C , we get: C = - 30
Putting the value of m back in the equation : y = m x + C
y = 3 x -30
Hence, the required equation models the total profit, y, based on the number of hot dogs sold, x is y = 3 x - 30.